Comparative efficacy and acceptability of psychological interventions for the treatment of adult outpatients with anorexia nervosa: a systematic review and network meta-analysis. (March 2021) - Solmi, M; Wade, T D; Byrne, S; Del Giovane, C; Fairburn, C G; Ostinelli, E G; De Crescenzo, F; Johnson, C; Schmidt, U; Treasure, J; Favaro, A; Zipfel, S; et al.
Summary: Background: No consistent first-option psychological interventions for adult outpatients with anorexia nervosa emerges from guidelines. We aimed to compare stand-alone psychological interventions for adult outpatients with anorexia nervosa with a specific focus on body-mass index, eating disorder symptoms, and all-cause dropout rate. Methods: In this systematic review and network meta-analysis, we assessed randomised controlled trials about stand-alone pharmacological or non-pharmacological treatments of adult outpatients with anorexia nervosa, defined according to standardised criteria, with data for at least two timepoints relating to either body-mass index or global eating disorder psychopathology. We searched Cochrane CENTRAL, CINAHL, MEDLINE, and PsychINFO for published and unpublished literature from inception until March 20, 2020. The primary outcomes were the change in body mass index and clinical symptoms, and the secondary outcome was all-cause dropout rate, which were all assessed for treatment as usual, cognitive behavioural therapy (CBT), Maudsley anorexia treatment for adults, family-based treatment, psychodynamic-oriented psychotherapies, a form of CBT targeting compulsive exercise, and cognitive remediation therapy followed by CBT. Global and local inconsistencies for the network meta-analysis were measured, and CINeMA was used to assess the confidence in evidence for primary outcomes. The protocol is registered in PROSPERO (CRD42017064429). Findings: Of 14 003 studies assessed for their title and abstract, 16 (0·1%) randomised controlled trials for psychological treatments were included in the systematic review, of which 13 (0·1%) contributed to the network meta-analysis, with 1047 patients in total (of whom 1020 [97·4%] were female). None of the interventions outperformed treatment as usual in our primary outcomes, but the all-cause dropout rate was lower for CBT than for psychodynamic-oriented psychotherapies (OR 0·54, 95% CI 0·31–0·93). Heterogeneity or inconsistency emerged only for a few comparisons. Confidence in the evidence was low to very low. Interpretation: Compared with treatment as usual, specific psychological treatments for adult outpatients with anorexia nervosa can be associated with modest improvements in terms of clinical course and quality of life, but no reliable evidence supports clear superiority or inferiority of the specific treatments that are recommended by clinical guidelines internationally. Our analysis is based on the best data from existing clinical studies, but these findings should not be seen as definitive or universally applicable. There is an urgent need to fund new research to develop and improve therapies for adults with anorexia nervosa. Meanwhile, to better understand the effects of available treatments, participant-level data should be made freely accessible to researchers to eventually identify whether specific subgroups of patients are more likely to respond to specific treatments. Funding: Flinders University, National Institute for Health Research Oxford Health Biomedical Research Centre.